Ayurvedic Approach to PCOS-A Critical Review - Verma, Sheela; Saxena, Anjana (International Research Journal of Ayurveda & Yoga, 2022)
Introduction-Polycystic Ovary Syndrome (PCOS) is a common chronic anovulatory disorder with androgen excess in women of reproductive age. It is a multifactorial, multisystem disorder but, obesity & insulin resistance are often associated. The patient with symptoms of menstrual irregularities, excess androgen (hirsutism, acne alopecia), and USG shreds of evidence of >2-9 mm size arranged in the cortex of the ovary. Aims: To explore and understand ayurvedic theories and practices on PCOS. Material and methods: The Charaka Samhita, a classical Ayurvedic book, was thoroughly examined to compile a list of relevant references together with Sanskrit commentary. Internet searched to locate study papers and related material. Conclusion: According to the Ayurveda PCOS is studied, and its pathogenesis tried to be established. Kapha Vata predominant tridoshaja vikara & agnimandhya is the main reason for pathogenesis. So, it can be effectively treated by tridosha pacifying, agnivardhak chikitsa with uttarvasti.